Penerapan Model Poe Berbasis Blended Learning Untuk Meningkatkan Keterampilan Berpikir Tingkat Tinggi Peserta Didik Kelas XI SMA - Amelia, Rini; Husniyah, Rif'il; Hidayatullah, Silmi; Permaisuri, Lili (Universitas Negeri Padang, 2021)
This classroom action research aims to improve students' higher order thinking skills by using the POE model based on blended learning in learning. The research method used is classroom action research. The subjects of this study were students of class XI MIPA1 SMA N Painan in the 2020/2021 semester II academic year, totaling 36 people. The object of this research is the students' higher order thinking ability. This research was conducted in two learning cycles, with the stages in each cycle being planning, action, observation/evaluation, and reflection. The higher order thinking ability in question is the score of students obtained in doing the higher order thinking skills test (C4, C5 and C6) which consists of 10 essay questions. This research is said to be successful if the average value of students' higher order thinking skills is 78, with classical completeness of 85%. The data that has been collected is then analyzed descriptively. The results of the analysis show 1) the average value of students' higher order thinking skills in the first cycle is 76.70 with 72% classical completeness and in the second cycle is 84.50 with 86% classical completeness.